Integral characteristics of water droplet evaporation in high-temperature combustion products of typical flammable liquids using SP and IPI methods; International Journal of Thermal Sciences; Vol. 108 - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna (2016, 2016)
Title screen